MANAGEMENT OF PHYSIOTHERAPY IN CHILD WITH ATTENTION DEFICIT HYPERACTIVITY DISORDER (ADHD): A CASE STUDY - Yustiansari, Ratna Aziami; Wijianto, W; Trisnaningrum, Devi Ayu (Academic Physiotherapy Conference Proceeding, 2021)
Introduction: Attention-deficit hyperactivity disorder (ADHD) is a chronic condition that affects millions of children and often persists into adulthood. ADHD is one of the most common neurodevelopmental disorders with a worldwide prevalence rate of 5% among children and adolescents. The ratio of men to women is 2:1. The risk factors for ADHD include blood relatives with ADHD or other mental health disorders, exposure to rac un environment , the use of drugs , alcohol or smoking by the mother during pregnancy, maternal exposure to the toxic environment and also birth prematurely . Case Presentation: The method used in this study is a case report from a patient at the Mitra Insan Mandiri (MIM) Clinic in Ponorogo with the identity of An. ANP aged 3 years 5 months. Management and Outcame: Administration of neuro sensory (NS), head massage, expression massage, sensory integration and paravertebral release with myofascial release (MRF) technique showed a fairly good effect on the problems that exist in patients with ADHD. Discussion: Giving n euro senso used to download sensory stimulation and to train children to be quiet. Sensory integration (SI) therapy focuses on increasing the child's capacity to integrate sensory and input. SI therapy uses a neurophysiological approach to implementation and can reduce hyperactivity and attention problems. Head massage is useful for sensory stimulation, reducing children's emotions and providing a sense of comfort so as to make children calmer. M assage expressions may provide sensory stimulation to the face. Paravertebral release with the Myofascial Release (MFR) technique is given to reduce spasm in the paravertebral area. Conclusion: The provision of therapy programs in the form of neuro sensory, sensory integration, head massage , expression massage and paravertebral release using the MFR technique can have a fairly good effect after 4 therapy sessions in dealing with problems caused by patients with ADHD.